2( − 1) + 2(3 − 1) = 0 PLEASE SOLVE

Question

2( − 1) + 2(3 − 1) = 0 PLEASE SOLVE

in progress 0
Faith 2 months 2021-11-28T15:02:27+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-28T15:03:58+00:00

    2( − 1) + 2(3 − 1) = 0

    solving By BODMAS rule

    2(-1)+2(2)=0

    -2+4=0

    LHS not equal to RHS

    0
    2021-11-28T15:04:21+00:00

    Answer:

    2 = 0

    Step-by-step explanation:

    2 ( -1 ) + 2 (3-1) = 0

    -2 + 2 (2) = 0

    -2 +4 = 0

    2 = 0

    they are not equal

    I HOPE THIS ANS HELPED YOU PLEASE MARK AS BRAINLIEST

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )